Transition of Nano-Architectures Through Self-Assembly of Lipidated β3-Tripeptide Foldamers - Habila, Nathan; Kulkarni, Ketav; Lee, Tzong-Hsien; Al-Garawi, Zahraa S.; Serpell, Louise C.; Aguilar, Marie-Isabel; Del Borgo, Mark P. (Frontiers in Chemistry, 2020)
β3-peptides consisting exclusively of β3-amino acids adopt a variety of non-natural helical structures and can self-assemble into well-defined hierarchical structures by axial head-to-tail self-assembly resulting in fibrous materials of varying sizes and shapes. To allow control of fibre morphology, a lipid moiety was introduced within a tri-β3-peptide sequence at each of the three amino acid positions and the N-terminus to gain finer control over the lateral assembly of fibres. Depending on the position of the lipid, the self-assembled structures formed either twisted ribbon-like fibres or distinctive multilaminar nanobelts. The nanobelt structures were comprised of multiple layers of peptide fibrils as revealed by puncturing the surface of the nanobelts with an AFM probe. This stacking phenomenon was completely inhibited through changes in pH, indicating that the layer stacking was mediated by electrostatic interactions. And peptides comprised of multiple positive charges resulted in the self-alignment of nanostructures. Overall, the results demonstrate that the nanostructures formed by the β3-tripeptide foldamers can be tuned via sequential lipidation of N-acetyl β3-tripeptides which control the lateral interactions between peptide fibrils and provide defined structures with a greater homogeneous population.